Analysis Of The Influence Of Financial Liquidity And Leverage On Profitability In Manufacturing Companies Listed On Idx 2015 – 2019 - Mu avidayana, Mu avidayana; Indupurnahayu, Indupurnahayu; Hurriyaturrohman, Hurriyaturrohman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
The purpose of this study was to determine and analyze the effect of liquidity and financial leverage on profitability by using 5 samples of companies listed on the Indonesia Stock Exchange from 13 populations of Manufacturing Companies in the Automotive Sub-Sector and their Components. Sampling technique (Purposive Sampling). The test method used to determine the effect of the dependent and independent variables is multiple linear regression analysis. The results of this study state that there is a positive and significant effect between Liquidity on Profitability with a value of t arithmetic (2.652) > tta table (2.07961) with a significance level of less than 0.05, namely (0.015 < 0.05). And there is a positive and significant influence between Leverage on profitability. This is evidenced by the value of t count (3.486) > t table (2.07961) with a significance level of less than 0.05, namely (0.002 < 0.05). Meanwhile, simultaneously there is the effect of Liquidity and Leverage on Profitability in Manufacturing Companies in the Automotive Sub-Sector and Its Components listed on the Indonesia Stock Exchange where the significance value of F is 0.008 where the significance value is less than 0.05.